Factors involved in the handling of iron by the reticulo-endothelial system - Lipschitz, D. A. (My University, 1972)
For centuries iron was regarded as a source of health and vigour, and it has been known for at least 200 years that it is a component of blood and effective in the treatment of chlorosis. However, its metabolism remained largely a mystery until the advent of radioactive iron isotopes in 1938. Since then most of the major pathways of this metal into, through and out of the body have been elucidated. In addition the functions which it subserves have been partially characterized.
A thesis presented for the degree of Doctor of Philosophy in Medicine of the University of the Witwatersrand, Johannesburg 1972
Keywords: Endothelium cells; Iron; Ferritins